CLINICAL CHARACTERISTICS OF PATIENTS WITH PTERYGOPALATINE HANHLIONIT - Колісник, І.А. (World of Medicine and Biology, 2016)
93 patients with pterygopalatine ganglionitis were examined. By clinical picture they were divi While dividing patient into groups we took into account the intensity and characteristics of pain, its original location, frequency of pain attacks and their duration. We noted the presence or absence of autonomic manifestations: salivation, lacrimation, rhinorrhea, skin redness, local fever, swelling of soft tissues. The disorders of sensitivity and pain on palpation of exit points of cranial nerves, as well as a symptom of "pinch" (skin folds) on the affected side were revealed. With the aim of objectification of data, and evaluation of pain intensity we used visual analog scale (Visual Analog Scale, VAS). Clinical picture of pterygopalatine ganglionitis of mild severity was detected in 22 patients, moderate severity was diagnosed in 43 patients and severe – 28 people. The degree of clinical severity of pterygopalatine ganglionitis it is advisable to consider in administration of treatment.
Keywords: pterygopalatine ganglionitis; clinical manifestations; severity of clinical course